Subjective mobilization of teaching work, the impacts generated by the Covid-19 pandemic: An approach to psychodynamics - Pires , Roseli Vieira; Duarte , Suelma Rodrigues; Pires, Rodrigo Corrêa (Seven Editora, 2023)
The objective is to answer how higher education teachers in the municipality of Porangatu, Goiás experience defensive and coping strategies in the exercise of their functions during the COVID-19 pandemic. It contains a brief history of education in Brazil, the psychodynamics of work and subjective mobilization. It uses the methodology of the Psychodynamics of Work with collective discussions. As a result, it is expected to know the experiences of the teachers. DOI:https://doi.org/10.56238/uniknowindevolp-046